The Role of miR‐21 in Cancer. Issue 6 (16th June 2015) - Pfeffer, Susan R.; Yang, Chuan He; Pfeffer, Lawrence M.; Gurwitz, David
ABSTRACT <table-wrap position="anchor" orientation="portrait"> Preclinical Research </table-wrap> MicroRNAs (miRNAs) are small endogenous noncoding RNAs that suppress gene expression at the post‐transcriptional level. In the past decade, miRNAs have been extensively studied in a number of different human cancers. MiRNAs have been identified to act both as oncogenes and as tumor suppressors. In addition, miRNAs are associated with the intrinsic resistance of cancer to various forms of therapy, and they are implicated in both tumor progression and metastasis. The characterization of the specific alterations in the patterns of miRNA expression in cancer has great potential for identifying biomarkers for early cancer detection, as well as for potential therapeutic intervention in cancer treatment. In this chapter, we describe the ever‐expanding role of miR‐21 and its target genes in different cancers, and provide insight into how this oncogenic miRNA regulates cancer cell proliferation, migration, and apoptosis by suppressing the expression of tumor suppressors. Drug Dev Res 76 : 270–277, 2015. © 2015 Wiley Periodicals, Inc.